CREATION OF A DESIGNER COLLECTION OF THEATER AND DANCE SHOES IN THE STYLE OF "ICHIGI" - BABYCH, ANTONINA; LYPSKI, TIMOFEY (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The demand for shoes in the theater and dance segment is large, although specific. However, it is not large enough for medium-sized enterprises, so these shoes are made in single copies to order in small workshops.Requirements for shoes, structures and manufacturing technologies in Ukraine as of 2025 are not sufficiently studied. The implementation of bold structural and technological solutions, the use of modern materials, simplicity, economy, creative design, practical production and testing of products in real-time conditions are an actual component of this project.Humanity is rapidly developing intellectually and technologically, its needs and preferences are transforming, therefore the dance has also changed and improved, and together with it, the stage costumes and shoes for its performance are also changing. Therefore, the issue of designing and manufacturing stage dance shoes individually, taking into account certain requirements, is relevant nowadays.In the work on the project, an analysis of thematic studies and publications of scientists and practitioners according to the topic was carried out. A historical tour of the origin, development and evolution of footwear, namely Ichiga boots, is presented, the design features, materials used and requirements for the products are described. The relevance of the development and the project has been theoretically proven.The complete and step-by-step process of manufacturing products was studied experimentally in order to improve the design and functionality of shoes at the stages of product creation.Sketches for the Ichiga shoe model, documentation for the products of the industrial collection series and calculations of the economic component of the project were developed.The line of theater and dance shoes "Ichiga" was produced in the conditions of "Litini" LLC and tested in the conditions of the Kyiv Opera and Ballet Theater.
Keywords: theater and dance shoes; design; material; style